A Decade of Pelvic Pain and Infertility: A Case Report of an Unexpected Intraoperative Discovery. Issue 2 (2017) - Stephens, Angela; Gavrilova-Jordan, Larisa P.; Ray, Chadburn
Introduction: Retained surgical objects can impact quality of life as it relates to chronic pelvic pain and reproductive health. Case report: A 39-year-old G1P0010 with chronic pelvic pain and infertility attributed to pelvic adhesions and bilateral hydrosalpinx caused by an 18-cm surgical drain left 10 years prior. Conclusions: Our case highlights the significance of thoughtful perioperative care as well as special considerations when approaching patients with pelvic pain and infertility with histories of abdominopelvic surgery.